Advances in mechanical assist devices and artificial hearts for children. Issue 5 (October 2015) - Kirklin, James K.
Abstract : Purpose of review: Mechanical circulatory support (MCS) has rapidly evolved toward continuous flow technology in adults. In the pediatric population, the Berlin EXCOR, a paracorporeal pulsatile pump, is the only MCS device specifically approved for pediatric use. The current era of pediatric MCS includes an increasing application of adult continuous flow pumps to pediatric patients. Recent findings: The Berlin EXCOR pulsatile pump has been studied in over 200 patients. The major limitations of this device are neurologic dysfunction (which occurs in about 30% of supported patients) and the requirement for in-hospital care until transplant. Two continuous flow pumps (HVAD and HeartMate II) have been successfully applied in children and adolescents, and the SynCardia total artificial heart has been used in adolescents. The National Heart, Lung, and Blood Institute – sponsored Pediatric Mechanically Assisted Circulatory Support registry has collected pediatric MCS data since 2012 and will provide valuable outcomes data to help refine this field. Survival with these durable devices has been generally good (except for small infants and patients with complex congenital heart disease), with nearly 50% receiving a heart transplant within 6 months. Patients with single ventricle physiology continue to pose major challenges. Two clinical trials for miniaturized adult continuous flow devices and one trial for a new pediatric pump will begin within the next year. Summary: New continuous flow devices are entering or poised to enter clinical trials. If approved, these devices will enhance the safety and variety of options for longer-term pediatric support.